Determination of heavy metals and genotoxicity of water from an artesian well in the city of Vazante- MG, Brazil - Silva, Regildo Márcio Gonçalves da [UNESP]; Amaral, Eni Aparecida do; Oliveira, Vanessa Marques de [UNESP]; Silva, Luciana Pereira [UNESP] (My University, 2013)
The city of Vazante-MG is of great socioeconomic and environmental interest because it is the most important zinc producer district of Brazil. The mineral processing and geochemical processes may determine high concentrations of heavy metals in water intended for human consumption. Thus, the present study aimed to quantify and evaluate the heavy metal genotoxicity of artesian water in the city by Atomic absorption spectrophotometer analysis and testing with the Allium cepa test, respectively. This study reveals a chemical contamination in well water in the city, caused by the presence of heavy metals. Therefore, it can be considered that the high levels of heavy metals found in water samples are correlated with the genotoxic events observed in root cells of A. cepa.
Keywords: Allium cepa; micronucleus; atomic absorption; chromosome aberration; mitotic index